The pragmatics of quoting now and then - Arendholz, Jenny; Bublitz, Wolfram; Kirner-Ludwig, Monika (Topics in English linguistics, 2015)
Frontmatter -- Acknowledgements -- Table of Contents -- Introducing Quoting as a Ubiquitous Meta-communicative Act -- 1. Reportable Facts and a Personal Touch: The Functions of Direct Quotes in Online News -- 2. Quoting in Online Message Boards: An Interpersonal Perspective -- 3. The Complexities of Thread-internal Quoting in English and German Online Discussion Fora -- 4. Quoting in Political Discourse: Professional Talk Meets Ordinary Postings -- 5. Quotation and Online Identity: The Voice of Tacitus in German Newspapers and Internet Discussions -- 6. “Ich kenne da so einen Jungen … kennen ist gut, wir waren halt mal zusammen weg.” On the Pragmatics and Metapragmatics of X ist gut in German -- 7. Only “nur”. Scare Quoted (Exclusive) Focus Particles at the Semantics/ Pragmatics Interface -- 8. Manufacturing Credibility: Academic Quoting Across Cultures -- 9. Quotative Markers in A Corpus of English Dialogues 1560–1760 -- 10. Histories of Talking about Talk: Quethen, Quoth, Quote -- 11. Quoting and Translating Latin in the Old English Homilies of the Vercelli Book -- 12. Quoting and Plagiarising – Concepts of Both Now and Then? -- 13. In-between Cognitively Isolated Quotes and References: Looking for Answers Lurking in Textual Margins -- 14. Quotations in Early Modern English Witness Depositions -- 15. Haunting Evidence: Quoting the Prisoner in 19th Century Old Bailey Trial Discourse. The Defences of Cooper (1842) and McNaughten (1843) -- 16. Quotations from 17th and 18th Century Medical Case Reports1 -- About the Authors -- Index of Subjects
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Geschichte; Sprechakt; Pragmatik; Redeerwähnung; Zitat